Social Intelligence and Consumer Feedback Loops in the Innovation Cycle of Electronics - Deepshikha Aggarwal; Archana B. Saxena; Deepti Sharma (Science and Technology: Developments and Applications Vol. 4, 2025)
The integration of social intelligence and consumer feedback loops has transformed the innovation cycle in the electronics industry, allowing for more agile and customer-focused product development. This research explores how social media platforms, online communities, and other digital feedback mechanisms serve as rich sources of real-time consumer insights, helping brands stay competitive in a rapidly evolving market. The research also emphasizes the growing role of artificial intelligence (AI) and machine learning (ML) in automating the collection and analysis of vast amounts of social media data. These technologies allow businesses to track trends, forecast customer needs, and implement product adjustments more efficiently. By integrating AI-driven insights into their innovation cycles, electronics manufacturers can not only enhance product quality but also improve customer engagement and loyalty. This paper examines the role of social intelligence and consumer feedback loops in the innovation cycle of electronic devices. In this study, data were collected from Social Media Platforms through Surveys and Interviews. Text mining tools were used to perform sentiment analysis on social media data to determine public perception of products. By analysing feedback on platforms like Twitter, Reddit, and Facebook, companies can gauge customer sentiment on key features such as battery life, software performance, and durability. The study results revealed that companies can improve by being more responsive to feedback and making customers feel that their feedback is acknowledged and acted upon. This study demonstrates the value of embedding social intelligence within the feedback loops of electronic innovation. As consumer expectations continue to rise, the ability to swiftly and effectively respond to feedback will become a critical competitive advantage for brands. The findings contribute to a deeper understanding of how consumer data can be leveraged to fuel a customer-centric innovation model, highlighting the significance of feedback loops in driving continuous improvement in product design and development. The rapid pace of technological advancements requires electronics manufacturers to stay agile, continuously monitoring consumer preferences and behaviours. Social intelligence, driven by data from social media and online platforms, offers a way to understand these evolving preferences. By integrating social intelligence with structured consumer feedback loops, companies can create more user-centred innovations and better adapt to market trends. The study analyses how these mechanisms have reshaped product development, including key challenges and opportunities.